Molybdenum, a versatile and vital element - Gutiérrez-Zorrilla, Juan M. (2019)
Molybdenum, produced in Peru as a byproduct of the copper mining industry, was discovered in the XVIIIth century. It is usually added to steel alloys, is amply used in different pigments and its presence in enzymes makes it a relevant element in life.